Gender-Specific Associations Between Saliva Microbiota and Body Size - Raju, Sajan C.; Lagström, Sonja; Ellonen, Pekka; de Vos, Willem M.; Eriksson, Johan G.; Weiderpass, Elisabete; Rounge, Trine B. (Frontiers in Microbiology, 2019)
Objective: The human intestinal microbiota likely play an important role in the development of overweight and obesity. However, the associations between saliva microbiota and body mass index (BMI) have been sparsely studied. The aim of this study was to identify the associations between saliva microbiota and body size in Finnish children. Methods: The saliva microbiota of 900 Finnish children, aged 11-14 years with measured height and weight, was characterized using 16S rRNA (V3-V4) sequencing. Results: The core saliva microbiota consisted of 14 genera that were present in more than 95% of the Finnish children. The saliva microbiota profiles were gender-specific with higher alpha-diversity in boys than girls and significant differences between the genders in community composition and abundances. Alpha-diversity differed between normal weight and overweight girls and between normal weight and obese boys. The composition was dissimilar between normal weight and obese girls, but not in boys. The relative abundance profiles differed according to body size. Decrease in commensal saliva bacteria were observed in all the body sizes when compared to normal weight children. Notably, the relative abundance of bacteria related to, Veillonella, Prevotella, Selenomonas and Streptococcus was reduced in obese children. Conclusions: Saliva microbiota diversity and composition were significantly associated with body size and gender in Finnish children. Body size–specific saliva microbiota profiles open new avenues for studying the potential roles of microbiota in weight development and management.